Angiodysplasia Combined with Thymic Aplasia in an Infant: A Rare Clinical Case - Svetlana A. Hmilevskaya; Galina N. Masljakowa; Nikolai I. Zryachkin; Olga A. Makarowa; Mikhail M. Bazalitsky; Tatiana V. Elizarova ("Paediatrician" Publishers LLC, 2018)
Background. The prevalence of congenital malformations of the vessels or angiodysplasia ranges from 1:50,000 to 1:5,000,000. Congenital angiodysplasia is a consequence of impaired formation and development of the vascular system in embryogenesis. The aetiology of angiodysplasia remains poorly studied, and the diagnosis involves significant difficulties in some cases. Clinical Case Description. The observation of a rare case of a combined malformation of vessels and thymic aplasia in a female infant is presented. Angiodysplasia included the syndrome of congenital generalised phlebectasia (synonym: congenital telangiectatic marbled skin) combined with multiple vascular malformations with predominant vascular lesions of the brain, lungs, heart, kidneys, and mesentery. Clinically, the disease was characterised by a generalised change in the skin in the form of livedo reticularis accompanied by the development of severe pneumonia, persistent urinary syndrome, neurological symptoms (convulsive seizures, motor disorders), and progressive heart failure. The diagnosis was confirmed in the course of a pathological study. Conclusion. The presented case allows expanding the notion of the variety of clinical manifestations of congenital angiodysplasia, as well as its possible combinations with other malformations.